(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
This article is devoted to the analysis of methods for creating a knowledge base of a digital library based on the semantic model of authority files. The article also describes the practical aspects of creating an electronic library legal encyclopedia based on the semantic model of authority files. Creation of a semantic network of authority files significantly optimizes the quality and speed of searching for resources in electronic libraries and creates the basis for intellectualization of information retrieval. The article examines in detail the existing approaches to creating a knowledge base of authority files, including files based on semantic models, and forming a knowledge base structure. The main purpose of the study is to create an improved model and develop software for creating a knowledge base of an electronic library of semantic authority files for various subject areas. In the article the theoretical research methods (method of comparison and critical thinking) and empirical research methods (data collection and document analysis) have been applied. Used object-oriented programming, intelligent information retrieval, reverse indexing capabilities. The field of jurisprudence was chosen for the application and approbation of the created model and software. A knowledge base has been created that studies frequently used specialized terms and semantic relationships between them.